2007
DOI: 10.1055/s-2007-965071
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Modified Conconi Running Test

Abstract: The aim of this study was to assess the validity of a fast ramp treadmill protocol for determination of the heart rate deflection point (HR (dp)) and speed of deflection (S (dp)) in trained runners. Fifty-one trained male runners performed a standard (T (stand); speed increase 1 km . h (-1) every 60 s) and a fast (T (fast); speed increase 1 km . h (-1) every 30 s) incremental treadmill test until volitional exhaustion. Heart rate was continuously recorded, and the HR (dp) was estimated after data averaging as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 26 publications
1
18
0
3
Order By: Relevance
“…This is consistent with the finding of Sentija et al [12], who found a very good reproducibility for HR dp comparing different kind of modified Conconi test protocols, while speed was dependent of the test protocol. Protocols with longer duration of the bouts resulted in a slower speed at DP, without changing HR dp compared with protocols with shorter bouts.…”
Section: Reproducibility Of Hr At Dp (Hr Dp )supporting
confidence: 92%
See 3 more Smart Citations
“…This is consistent with the finding of Sentija et al [12], who found a very good reproducibility for HR dp comparing different kind of modified Conconi test protocols, while speed was dependent of the test protocol. Protocols with longer duration of the bouts resulted in a slower speed at DP, without changing HR dp compared with protocols with shorter bouts.…”
Section: Reproducibility Of Hr At Dp (Hr Dp )supporting
confidence: 92%
“…According to the existing literature, we can conclude that DP can be identified in the majority of the HR/PO graphs, but in few cases (0 to 7.6%) it may be impossible to see a deflection [3,12,14]. In our experience, the lack of a DP mostly appears in people that are not used to perform to exhaustion and stop the test as soon as acidaemia appears.…”
Section: Identification Of a Dpmentioning
confidence: 54%
See 2 more Smart Citations
“…Internationally, the "maximum lactate steady-state" (MLss) is defined as the highest constant lactate level which can be maintained by the athlete over 30 minutes (8). In this phase II, sometimes called aerobic-anaerobic transition, elimination can still compensate lactate production (9). Finally, in phase III lactate will increase almost exponentially and therefore in athletes this phase will last only for a limited time interval as steady state conditions have been lost.…”
Section: Introductionmentioning
confidence: 99%